Doctors Dealing With COVID-19 in Pakistan: Experiences, Perceptions, Fear, and Responsibility - Ali, Inayat; Sadique, Salma; Ali, Shahbaz (Frontiers in Public Health, 2021)
This article describes the dealings of 20 biomedical doctors with COVID-19 in Pakistan’s Sindh Province. Focusing on physicians from three different hospitals, we describe their challenges, emotions, and views concerning the pandemic. Many regarded the virus from a biomedical standpoint. Yet some perceive it as a “tool of a proxy war” and a “plot” without giving agency to anyone for that “plot.” Furthermore, these care providers faced a great fear of infection and an even greater fear of transmitting the virus to their families and friends. A few also stated about facing stigmatization. Whether they experienced fear or not, all of our physician interlocutors emphasized their sense of responsibility to “serve humanity,” yet some expressed a strong belief in the inevitability of the will of Allah. Some were satisfied with the government’s role in containing the virus, while others expressed concerns and felt that the government should be doing much more. All expressed confidence in the use of personal protective equipment, viewing it as an effective buffer against viral contagion. We conclude with a call for further research on physicians’ dealings with COVID-19 across Pakistan as frontline care providers.